Fenomena Busana Hajja Pasca Haji di Kabupaten Bone Perspektif Al-Qur’an - Mursalin; Amir Hamzah; Abdul Ghany (Sekolah Tinggi Ilmu Al-Qur'an (STIQ) Bima, 2025)
This study discusses the phenomenon of Hajja clothing worn by women who have performed the pilgrimage (hajj) in Bone Regency. This research is categorized as field research and presented in a descriptive qualitative form, employing anthropological, sociological, and exegetical approaches. Data processing and analysis were carried out through the stages of data reduction, data presentation, and conclusion drawing. The findings indicate that Hajja attire is not worn in daily life but rather on special occasions such as weddings, as a form of respect for religious and social values. Distinctive attributes such as tallili or mappatoppo serve as symbols of honor and pride for Bugis Bone women after completing the pilgrimage. The use of clothing and accessories such as tallili, misba, and gelang haji (pilgrim’s bracelet) represents both a religious expression and a form of spiritual pride following the pilgrimage. Post-hajj Hajja clothing in Bone Regency is not merely a marker of spiritual journey but has evolved into a symbol of social status and religious identity within society. Culturally, Hajja clothing embodies the fusion of Islamic values and local Bugis Bone traditions that emphasize modesty, honor, and dignity. From the Qur’anic perspective, the wearing of garments during and after the pilgrimage holds not only physical but also spiritual significance, serving as a manifestation of piety and purity of heart.